The ‘Coney Island caliphate’ and radicalised youth - Kumar Ramakrishna (2023)
The news of the arrest of a self-radicalised youth for an unusual terror plot, that amongst other things, included plans to engage in knife attacks on unbelievers, should be taken seriously. It sheds light on the ongoing challenge of youth radicalisation in recent years. That said, a sense of perspective is also in order. In the recent case, it seems clear that this was basically a youth with an overblown imagination, in dire need of stronger peer support and mentoring.